Strategi Dakwah dan Konseling Digital Berbasis Audiens di Era Media Sosial - Khulashotud Dianah; Mazarina Dewi Auliya; Shabrina Aulia ‘Izza; Shefiyah Medina (STIKes Ibnu Sina Ajibarang, 2025)
This study examines audience-based digital da'wah and counseling strategies to address communication challenges in the modern era. Digital da'wah is the delivery of Islamic teachings through social media and online platforms, while digital counseling provides psychological and spiritual support through digital communication channels. This study employed a literature review method, analyzing various relevant academic sources. The findings indicate that understanding the audience is crucial to ensuring da'wah and counseling messages remain relevant, targeted, and impactful. Audience segmentation based on age, cultural background, digital literacy, and spiritual and psychological needs is crucial in designing communication strategies. Adjusting language style, selecting appropriate media, and utilizing creative communication methods can increase audience engagement and strengthen the effectiveness of da'wah and counseling. By understanding audience characteristics in depth, digital da'wah and counseling strategies can be delivered more effectively, have a positive impact, and meet the spiritual and psychological needs of society in this digital era.